EDUCAȚIE PENTRU DREPTURILE OMULUI – DRUMUL SPRE DEMNITATE UMANĂ ȘI LIBERTĂȚI FUNDAMENTALE (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Education for Human Rights - The Path to Human Dignity and Fundamental FreedomsHuman rights represent a topic of major interest which has aroused controversies between different countries of the world, but which, through the mechanisms and instruments used, have ensured the protection and respect of human rights and fundamental freedoms. Despite the existing deficiencies in implementing human rights law, despite the fact that discrimination in all its forms is still present and many of the stated rights are not respected, human rights are the essential elements, indispensable for the defense of human personality against all forms of tyranny. We must not lose sight of the social and political context that led to the emergence of international bodies, nor the fact that, as Montgomery noted, human rights should be a permanent topic of debate in order to ensure respect for human dignity. An important impediment in the application of the laws adopted at the level of the two major international organizations - the United Nations and the European Union - is the lack of communication between international norms and local realities for reasons related to ignorance, indifference, carelessness and lack of education in this field. Therefore, in order to ensure full absorption of international provisions within each partner state, an important investment in the field of human rights education is required to be carried out both in the formal and nonformal frameworks, to generate knowledge., empowerment and reactions to the violation of any fundamental right. Ultimately, the main goal is to respect the dignity and integrity of the human being.